1998
DOI: 10.1021/bi981090b
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of an Exocyclic Cytosine Adduct on DNA Duplex Properties:  Significant Thermodynamic Consequences Despite Modest Lesion-Induced Structural Alterations

Abstract: The exocyclic base adduct 3,N4-deoxyethenocytosine (epsilonC) is a common DNA lesion that can arise from carcinogen exposure and/or as a biproduct of cellular processes. We have examined the thermal and thermodynamic impact of this lesion on DNA duplex properties, as well as the structural alterations imparted by the lesion. For these studies, we used calorimetric and spectroscopic techniques to investigate a family of 13-mer DNA duplexes of the form (5'CGCATGNGTACGC3')x(3'GCGTACNCATGCG5'), where the central N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
44
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 28 publications
(51 citation statements)
references
References 26 publications
7
44
0
Order By: Relevance
“…Studies are currently under way in our laboratory to examine the effect of both DNA sequence context and base pairing partner on the thermodynamic impact of the Sp lesion. The most destabilized lesion in this survey, on the basis of ∆∆G 37 values, is 3,N 4 -deoxyethenocytosine, which can arise from exposure to vinyl chloride, hepatic copper poisoning, or reaction of DNA with products of lipid peroxidation (49). This adduct very dramatically reduces the thermodynamic stability of the duplex with a ∆∆G 37 of 15 kcal/mol, representing a ∼85% loss in the total duplex thermodynamic stability (49).…”
Section: Resultsmentioning
confidence: 94%
“…Studies are currently under way in our laboratory to examine the effect of both DNA sequence context and base pairing partner on the thermodynamic impact of the Sp lesion. The most destabilized lesion in this survey, on the basis of ∆∆G 37 values, is 3,N 4 -deoxyethenocytosine, which can arise from exposure to vinyl chloride, hepatic copper poisoning, or reaction of DNA with products of lipid peroxidation (49). This adduct very dramatically reduces the thermodynamic stability of the duplex with a ∆∆G 37 of 15 kcal/mol, representing a ∼85% loss in the total duplex thermodynamic stability (49).…”
Section: Resultsmentioning
confidence: 94%
“…One melting temperature study found that on average a G ⅐T mismatch contributes 3.5 kcal/mol less energy than a G ⅐C base pair to the stability of a DNA duplex (37). In another study, 13 bp DNA duplexes containing a G ⅐ ⑀ C base pair were 13.4 -15.3 kcal/mol less stable than the parental G ⅐C-containing duplexes (38). A further study directly comparing the melting temperature of 15-bp DNA duplexes containing either a G ⅐ ⑀ C base pair or a G ⅐T mismatch found that the G ⅐ ⑀ C containing duplexes were 0.43-1.63 kcal/mol less stable than the corresponding G ⅐T-containing duplex (39).…”
Section: Discussionmentioning
confidence: 99%
“…Experimental results showed that the T‚G and C‚G mismatches apparently do not either have similar geometry or induce similar structural changes (4)(5)(6)(7)(8). Therefore, the observation that the same enzyme recognizes two structurally dissimilar substrates (2,3) raises the following question (11): What is the common motif in substrate recognition and selection by the human G/T(U) mismatch-DNA glycosylase?…”
Section: Introductionmentioning
confidence: 99%